A process model of buyer responses to salesperson transgressions and recovery efforts: the impact of salesperson orientation. Issue 1 (2nd January 2016) - Hansen, John D.; Lund, Donald J.; DeCarlo, Thomas E.
Abstract : Despite the damaging effects often associated with salesperson transgressions, our understanding of how buyers respond to these transgressions and the recovery efforts that typically follow is limited. The authors address this shortcoming across two studies of professional buyers. In the first, the authors examine buyers' responses to salesperson ethical and service transgressions as moderated by their perceptions of the salesperson (i.e. whether they perceive the salesperson as being selling-oriented (SO) or customer-oriented (CO)). In the second study, the authors contrast the effects of an apology versus compensation in examining buyers' responses to the overall transgression and recovery episode. Although study results indicate that a customer orientation amplifies buyers' responses to the initial transgression, they also indicate that buyers' responses to the overall episode are primarily a function of whether the recovery effort conforms to their expectations. Hence, while favorable salesperson perceptions (i.e. being perceived as CO) are detrimental in the context of the initial transgression, they are beneficial in the context of the overall transgression and recovery episode.